Enriching Architecture Craft and its conservation in Anglo-Irish building production, 1660-1760 - Casey, Christine; Hayes, Melanie (UCL Press, 2023)
Refinement and enrichment of surfaces in stone, wood and plaster is a fundamental aspect of early modern architecture which has been marginalised by architectural history. Enriching Architecture aims to retrieve and rehabilitate surface achievement as a vital element of early modern buildings in Britain and Ireland. Rejected by modernism, demeaned by the conceptual 'turn' and too often reduced to its representative or social functions, we argue for the historical legitimacy of creative craft skill as a primary agent in architectural production. However, in contrast to the connoisseurial and developmental perspectives of the past, this book is concerned with how surfaces were designed, achieved and experienced. The contributors draw upon the major rethinking of craft and materials within the wider cultural sphere in recent years to deconstruct traditional, oppositional ways of thinking about architectural production. This is not a craft for craft's sake argument but an effort to embed the tangible findings of conservation and curatorial research within an evidence-led architectural history that illuminates the processes of early modern craftsmanship. The book explores broad themes of surface treatment such as wainscot, rustication, plasterwork, and staircase embellishment together with chapters focused on virtuoso buildings and set pieces which illuminate these themes.